Prevalence of obesity and level of physical activity among health care professionals in rural hospitals in Sekhukhune District, Limpopo Province, South Africa - Senwamadi, Seemole Blantina (My University, 2018)
Background: Obesity and physical inactivity have been reported as the major contributing factors to non-communicable diseases and a public health problem worldwide. According to World health organization the global prevalence of obesity has increased more than doubled between 1980 and 2014. Many healthcare professionals fail to achieve sufficient levels of physical activity and most of them display poor dietary habits. The study conducted in South Africa among health care professionals in urban hospital in Gauteng province confirmed that 20% of them developed at least one NCD of which the contributing factors are obesity and physical inactivity. The aim of the study was to determine the prevalence of obesity and level of physical activity among health care professional in rural hospitals in Sekhukhune district, Limpopo province, South Africa. Methods: A quantitative descriptive study was conducted on 400 HCPs. The global questionnaire was closed ended. GPAQ was used for physical activity and anthropometric measurements were taken for BMI. A stratified random sampling method was used to sample HCPs. Data was analysed using SPSS version 23.0. Results: Most participants were females (71%), majority were between 30-39 years of age (46.3%), the highest category were nurses (77.8%), most of them their job title were assistants (44.5) and blacks (99.3%). The results revealed that 40.8% of HCPs were obese and 30.3% were overweight. Majority of (79.3%) were not engaging on work vigorous PA, however were engaging on work moderate PA. Also (60.5%) were not engaging on leisure vigorous PA, though 55.5% were engaging on leisure moderate PA. Majority (88.3%) had high sedentary (sitting) time. (35.50%) engaged in high activity of walking from one place to the other. In conclusion: There is a need for regular health promotion programmes among health care professionals with regard to obesity and importance of physical activity. The hospitals need to be equipped with onsite fitness centre that will be accessible to all HCPs. Physical activities support groups need to be established such as aerobics classes and fun run. Policies that guide participation in physical activities need to be drawn and be implemented accordingly in health sector, so as to promote healthy living habits. Key words: Obesity, Overweight, Level of physical activity, Health care professionals
Thesis (MPH.) --University of Limpopo, 2018
Keywords: Obese professionals; Physical activity; Sekhukhune District; Overweight; Exercise; Obesity in women; Obesity in men